Guerre et « subversion patriotique » : les républicains italiens face au premier conflit mondial et à ses usages politiques - Stéfanie Prezioso (Laboratoire Italien)
For a long time, the First World War was seen as a positive step in the constitution of the new Italian state, its first successfully met national challenge, when Italy became a full member of the club of great powers. I suggest that the trajectory of the activists of the Italian Republican Party (PRI) offers the best angle from which to illuminate both the emergence of this myth of the Great War and its persistence after the Second World War. During the months of non-intervention, the Republicans’ support for intervention included an effort to “give the war meaning”. The young Republicans argued that joining the war was the necessary step for Italy’s entry into political modernity. They saw themselves as subversive patriots whose goal was a radical but necessary transformation of Italian society, one that would affect not only the country’s political, social, and economic foundations but also the very “character” of Italians. After a brief flirtation with the then emerging Fascist movement, it was precisely their interventionism that became the foundation of their radical anti-fascism.